Preliminary mission profile of Hera's Milani CubeSat. Issue 6 (15th March 2021) - Ferrari, Fabio; Franzese, Vittorio; Pugliatti, Mattia; Giordano, Carmine; Topputo, Francesco
Abstract: CubeSats offer a flexible and low-cost option to increase the scientific and technological return of small-body exploration missions. ESA's Hera mission, the European component of the Asteroid Impact and Deflection Assessment (AIDA) international collaboration, plans on deploying two CubeSats in the proximity of binary system 65803 Didymos, after arrival in 2027. In this work, we discuss the feasibility and preliminary mission profile of Hera's Milani CubeSat. The CubeSat mission is designed to achieve both scientific and technological objectives. We identify the design challenges and discuss design criteria to find suitable solutions in terms of mission analysis, operational trajectories, and Guidance, Navigation, & Control (GNC) design. We present initial trajectories and GNC baseline, as a result of trade-off analyses. We assess the feasibility of the Milani CubeSat mission and provide a preliminary solution to cover the operational mission profile of Milani in the close-proximity of Didymos system.